Issues impacting Sales Promotion in International Marketing - Jadhav, Smita; Kumar, Atul; Brar, Vinaydeep (Future Science / FSH-PH Publications, 2022)
Sales promotion in international marketing is somewhat different from domestic markets for a few reasons. Adequate information may not be available with the exporter to make sales promotion decisions. At the same time, customers from the foreign markets may not know the exporter and his products well. Further, the exporter might face resource constraints while executing sales promotion plans in the international markets. Thus, sales promotion in global marketing is a different ball game and requires an understanding of issues that impact the sales promotion plans in the international markets. In this paper, we enlist some such areas which need to be considered by exporters while working out their sales promotion strategies for the export markets. This has been done by way of a survey of 120 exporters. Ten critical factors have been identified that have a bearing on the sales promotion efforts of international marketing.